OLYMPIC EDUCATION IN EXILE? - Juravle Mariana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Olympic education is not just a problem that concerns the Olympic family but a problem concerning education, sports, research, governments, and media with its huge role in creating a methodological environment that passes on information. The curriculum must comprise Olympic education in its content, in order to integrate the Olympic values in human behaviour and school must last as the main institution which develops the basis of a systematic Olympic education.